The Modern Islamic Education Thinking (Isma'il Raji Al-Faruqi (1921-1986 SM) and Syed Muhammad Naquif Al-Attas (1931)) - Mila Hasanah (Tarbiyah : Jurnal Ilmiah Kependidikan, 2017)
The development of Islamic educational thinking, has sketched ideas varied, ranging from the classic to the modern era. Thought modern Islamic education is a critical response on global Western secular civilization. The negative influence is the dualism of the education system that applies to Muslims, namely the Western education system and the system of Islamic education. Western education system is so powerful that its influence is a threat to Islamic education. Therefore, efforts are integral formation system is a must. Al-Faruqi and Al-Attas trying to bargain a solution in the form of Islamization of science, which differ in terms of strategy Islamization of science, if Al-Faruqi in social sciences while Al-Attas on the humanities. Typology thought al-Faruqi and Al-Attas is inseparable from social background and cultural nuances where both activity and appreciate their ideas.